The Polar Auxin Transport Inhibitor N-1-Naphthylphthalamic Acid Disrupts Leaf Initiation, KNOX Protein Regulation, and Formation of Leaf Margins in Maize - Scanlon, Michael J. (The American Society for Plant Biologists, 2003)
Maize (Zea mays) leaves develop basipetally (tip to base); the upper blade emerges from the shoot apical meristem (SAM) before the expansion of the lower sheath. Founder cells, leaf initials located in the periphery of the SAM, are distinguished from the SAM proper by the differential accumulation of KNOX proteins. KNOX proteins accumulate in the SAM, but are excluded from maize leaf primordia and leaf founder cells. As in Arabidopsis and tomato (Lycopersicon esculentum), maize shoots failed to initiate new leaves when cultured in the polar auxin transport inhibitor N-1-naphthylphthalamic acid (NPA). We demonstrate that NPA-induced arrest of leaf initiation in maize is correlated with the failure to down-regulate KNOX accumulation in the SAM. In addition, NPA-cultured shoots formed abnormal tubular leaf bases in which the margins failed to separate in the lower leaf zone. The tubular leaf bases always formed in the fourth leaf from the arrested meristem. Moreover, the unseparated margin domains of these tubular leaf bases accumulated ectopic KNOX protein(s). Transfer of NPA-cultured apices to NPA-free media resulted in the resumption of leaf initiation from the SAM and the restoration of normal patterns of KNOX down-regulation, accordingly. These data suggest that the lower sheath margins emerge from the leaf base late in maize leaf development and that the separation of these leaf margin domains is correlated with auxin transport and down-regulation of KNOX proteins. In addition, these results suggest that the down-regulation of KNOX accumulation in maize apices is not upstream of polar auxin transport, although a more complicated feedback network may exist. A model for L1-derived margin development in maize leaves is presented.